Preparation and Evaluation of Azithromycin as Rectal Suppository to Treat Bacterial Infection of COVID-19 - Khalil , Mena Raid; Hameed, Ghaidaa Sulaiman; Basil Hanna, Dalya (Iraqi Journal of Pharmaceutical Sciences, 2023)
In this study azithromycin was formulated for the first time as co-amorphous system suppository system to achieve the maximum bioavailability and to avoid the side effect that might be with oral route which is associated with this drug during treatment of Corona virus secondary bacterial infection. In this study the co-amorphous system was characterized by Differential Scanning Calorimetry (DSC), Powder X-ray Diffractometry (PXRD) and Fourier Transform Infrared Spectroscopy (FTIR). Eight different suppository formulas were prepared, these formulas were subjected to the dissolution test by Ph. Eur. Apparatus I (basket apparatus). The antibacterial activity was measured by the agar well-diffusion method. The results revealed the formation co-amorphous system. The formula in co-amorphous system with glycerin showed the best release for both azithromycin and curcumin. The combination and co-amorphous system showed double value of zone of inhibition rather than the drugs alone. This study will be interested in drugs company to find alternative rout of drug administration for serious infection that associated with GIT symptoms.